2020
DOI: 10.1021/acs.langmuir.0c02114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation of Contact Line Movement in Electrowetted Nanodroplets

Abstract: Molecular dynamics (MD) simulation of an electrowetted nanodroplet is performed to understand the fundamental origin of the involved parameters resulted from the molecular movement in the vicinity of the three-phase contact line (TPCL). During the spreading of the droplet, contact line friction (CLF) force is found to be the controlling one among all other resistive forces. Being molecular in nature, MD study is required to unveil the CLF, which is manifested by the TPCL friction coefficient ζ. The combined ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Other parameters for interactions with hydrogen were set to zero. A cutoff length of 10 Å was used for electrostatic and van der Waals forces based on the guidelines laid out by Chen et al Several prior MD simulation studies ,, of electrowetting of nano-sized droplet have used a similar cutoff to account for electrostatic forces. Lorentz–Berthelot mixing rules , were used to calculate any unknown coefficients.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other parameters for interactions with hydrogen were set to zero. A cutoff length of 10 Å was used for electrostatic and van der Waals forces based on the guidelines laid out by Chen et al Several prior MD simulation studies ,, of electrowetting of nano-sized droplet have used a similar cutoff to account for electrostatic forces. Lorentz–Berthelot mixing rules , were used to calculate any unknown coefficients.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In the presence of a continuous electric field, a droplet resting on a large path would attain an equilibrium configuration that may or may not be asymmetric. This has been extensively explored in prior studies. Daub et al concluded that the contact angle of a droplet in the presence of perpendicular and parallel electric fields is highly sensitive to the direction and polarity of the field. Song et al , later concluded that the asymmetry in the contact angles vanishes beyond a certain field strength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with solids, fluids are flexible and easy to control. The control of fluid movement, fusion, separation, and surface morphology is widely used in many fields, such as chemistry, biology, medicine, micro-electromechanical manufacturing, and so on. The most traditional way to control fluids is to provide pressure from the outside. There are many methods to control the micro-multiphase fluid in microfluidic technology, mainly including the passive mode and active mode.…”
Section: Introductionmentioning
confidence: 99%